Pencegahan Perilaku Bullying Melalui Program Psikoedukasi Berbasis Nilai Moral Islami di SMP Darussalam Kepanjen - Mohammad Hilfi Azra Dzikrulloh; Dinda Putri Abadi; Nadia Erlina Mayangsari; Luhur Kuncoroanggo; Yusron Risqy Maulana; Ni’matun Nashiroh; Putri Rahma Abadi; Putri Rismawati; Yenin Nadhifah; Maulida Kurniawati; Melinda Cahyawati; Hayuni Retno Widarti (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
School is a very important place where many aspects of life are taught. However, lately news about bullying cases in schools is often found. Bullying can be categorized as bad behavior or deviant behavior, this is because this behavior has a serious impact on the victim. Based on the various problems and solution studies that have been described, it is necessary to make efforts to prevent bullying behavior. One solution to prevent bullying behavior is a psychoeducation program that is integrated with Islamic moral values such as tolerance and courtesy as one of the reinforcements and supports the success of a guidance for behavior change. The method carried out in this activity is divided into several stages, namely (1) preparation stage, (2) implementation stage, and (3) evaluation stage. This activity produces several products, namely digital posters and guidebooks for teachers and students. The final results of Islamic moral psychoeducation show that students have an understanding of the behaviors that include bullying and understand how to prevent bullying behavior based on Islamic moral values.